Congenital Heart Surgery: Analysis of 102 Cases (Bangladesh Heart Journal, 2016)
Congenital heart diseases (CHDs) are a group of problems in the structure of the heart that is present at birth. Signs and symptoms depend on the specific type of problem. Symptoms can vary from none to life-threatening. CHD is prevalent throughout the world including Bangladesh. It is the leading cause of birth defect-related death. Most of the patients with CHDs need corrective surgery and life-long follow up with heart care. In this series, 102 cases of CHD patients were operated, 82 of them were of atrial septal defect (ASD), 12 ventricular septal defect (VSD), 2 Tetralogy of Fallot (TOF) and 6 patent ductus arteriosus (PDA). Operative and post-operative periods were uneventful. There were no major complications including death.Bangladesh Heart Journal 2015; 30(2) : 58-60